2022
DOI: 10.1002/path.6029
|View full text |Cite
|
Sign up to set email alerts
|

Human scattered tubular cells represent a heterogeneous population of glycolytic dedifferentiated proximal tubule cells

Abstract: Scattered tubular cells (STCs) are a phenotypically distinct cell population in the proximal tubule that increase in number after acute kidney injury. We aimed to characterize the human STC population. Three-dimensional human tissue analysis revealed that STCs are preferentially located within inner bends of the tubule and are barely present in young kidney tissue (<2 years), and their number increases with age. Increased STC numbers were associated with acute tubular injury (kidney injury molecule 1) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Until recently, Pax8 was not thought to be involved in AKI recovery 43,44 , though recent studies with newer techniques now suggest Pax8 is dynamically regulated during repair 6,12,13,28,33 . In addition, human 45,46 and rodent 42 proximal tubules contains scattered cells marked by higher levels of Pax2 and/or Pax8 that may have progenitor-like properties and may contribute disproportionately to repair. Work in the early 2000’s suggested that Pax2 was involved in maintaining proliferation and preventing apoptosis of injured cells 43,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, Pax8 was not thought to be involved in AKI recovery 43,44 , though recent studies with newer techniques now suggest Pax8 is dynamically regulated during repair 6,12,13,28,33 . In addition, human 45,46 and rodent 42 proximal tubules contains scattered cells marked by higher levels of Pax2 and/or Pax8 that may have progenitor-like properties and may contribute disproportionately to repair. Work in the early 2000’s suggested that Pax2 was involved in maintaining proliferation and preventing apoptosis of injured cells 43,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…59 In aging kidneys, a subset of PROM1-positive tubular epithelial cells has been identified that are both functionally impaired and have a distinct profibrotic phenotype. 60 Our biomarker discovery approach relied on the isolation of uEVs using ultracentrifugation. Ultracentrifugation-based uEV isolation for protein quantification is still the gold standard in the field, but is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…59 In aging kidneys, a subset of PROM1-positive tubular epithelial cells has been identified that are both functionally impaired and have a distinct profibrotic phenotype. 60…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the HRTPT cells have shown they are capable of differentiation into multiple cell types, form tubular structures in Matrigel, and can form nephrospheres. The origin of these progenitor cells has been the subject of debate with some studies proposing a unique population of cells scattered within the kidney and others proposing the co-expressing cells simply represent de-differentiated proximal tubule cells [22]. A recent study provides strong evidence that the cells co-expressing PROM1 and CD24 in the in vivo human kidney are heterogeneous populations of dedifferentiated proximal tubule cells [22].…”
Section: Discussionmentioning
confidence: 99%